Recovery of Copidosoma sp. (Hymenoptera : Encyrtidae), eggs parasidoid of Neoleucinodes elegantalis (Lepidoptera: Pyralidae) on Cyphomandra betacea - TRÓCHEZ-A., GUSTAVO ADOLFO; DÍAZ, ANA ELIZABETH; GARCÍA-ROA, FULVIA (Revista Colombiana de Entomología, 1999)
The egg parasitoid Copidosoma sp. is considered a potential biocontrol agent against the fruit borer (N. elegantalis) of tree tomatoes grown in upland areas of the Andes (1800 masl; 18%; 80% RH). Parasitism level, near 73%, has been observed in some areas; which suggested a high potential for biocontrol and promoted studies seeking the development of recovery methods of the parasitoid from infested fruits. Adults of Copidosoma sp. recovered from infested tree tomato fruits were delivered to tree tomato orchards, fruit damage was assessed and compared to fruit losses found in untreated fields (controls). Preliminary results indicate apparent reductions in fruit damage (3-8%) as compared to losses in untreated control fields (44-100% loss). The high efficiency of Copidosoma sp. in controlling N. elegantalis infestation allows growers to reduce the number of insecticide sprays.